Financial Development as a Buffer Against Demographic Dependency: Evidence from Human Development Outcomes in Sub-Saharan Africa - Lamin Panneh; Modou Secka; Ebrima khan (Indonesian Journal Publisher, 2026)
Sub-Saharan Africa (SSA) faces both a persistently high demographic dependency burden and comparatively underdeveloped financial systems. It is unclear whether deeper financial systems can offset the harm that dependency does to human development. This study examines whether financial development moderates the relationship between age dependency and human development outcomes in SSA. Using panel data for 43 SSA countries from 2004 to 2023, the study applies fixed-effects estimation with Driscoll-Kraay standard errors to test this relationship between the age dependency ratio and the Human Development Index (HDI). Our findings shows that age dependency ratio exerts a significant negative effect on HDI. Financial development, proxied by both domestic credit to the private sector and broad money, exerts a significant positive effect. The interaction between age dependency and financial development is positive and significant across both proxies. This shows that financial development weakens the adverse effect of dependency on human development, and the effect is stronger when financial development is measured by credit to the private sector. The result holds under a lagged robustness check and is corroborated by subsample analysis, which shows the negative dependency effect is significant only in low-financial-development countries. These findings extend buffer-stock theory from household consumption smoothing to macro-level human development outcomes. They suggest that deepening private credit markets is a viable policy lever for cushioning the human development costs of demographic aging in SSA.